The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/jcpe.12234
|View full text |Cite
|
Sign up to set email alerts
|

Salivary biomarkers of bacterial burden, inflammatory response, and tissue destruction in periodontitis

Abstract: Salivary concentrations of MMP-8, IL-1β, and P. gingivalis are associated with various clinical and radiographic measures of periodontitis. The CRS index, combining the three salivary biomarkers, is associated with periodontitis more strongly than any of the markers alone regardless of the coronary artery disease status of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
139
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 121 publications
(155 citation statements)
references
References 29 publications
7
139
1
3
Order By: Relevance
“…This results in increased levels of MMP-8 during periodontitis. Various studies have demonstrated increased MMP-8 levels related to periodontitis severity and course [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…This results in increased levels of MMP-8 during periodontitis. Various studies have demonstrated increased MMP-8 levels related to periodontitis severity and course [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers that are known to influence the prediction and progression of periodontal diseases should be investigated for statistical correlation to each other. Examples of biomarkers which can contribute to this are IL-1 β and MMP-8 whereby Salminen et al [129] used three salivary biomarkers together to diagnose periodontal disease. …”
Section: Recommendations For Future Studiesmentioning
confidence: 99%
“…However, its major shortcoming is that the gingival sulcus must be probed by a dentist; this probing may also be painful. Thus, other approaches including salivary diagnostics that can be performed by nonexpert examiners have been suggested [2]. …”
Section: Introductionmentioning
confidence: 99%